PUBLIC POLICY FORMULATION ANALYSIS PATTERNS IN GARUT DISTRICT REGIONAL REGULATION NUMBER 82 OF 2021 CONCERNING YOUTH - Hermawan, Yusuf; Triana H. S., Yagus; Fadhlurrohman, Mochammad Iqbal; Alpahmi, Moch Ari Ridwan (CosmoGov: Jurnal Ilmu Pemerintahan, 2024)
This research aims to examine the process of formulating regional regulation policy number 2 of 2021 which specifically addresses problems related to the youth population in Garut Regency. Public policy encompasses a series of actions and choices taken by government agencies, which include proactive actions and non-proactive actions. This research uses a qualitative approach and uses data triangulation as a tool for collecting information. The results of this research indicate that a committee has been formed to develop policies and strategies to address this problem effectively. Non-official players, such as youth organizations and journalists, also play a role in determining the goals of scientific publications. Policy alternatives are chosen as a way to address problems relating to the youth population, and the results are recorded in scientific publications and offered for scientific discourse. Regional regulations in the initial stage are officially ratified by the Regional People's Representative Council (DPRD), then ratified by the regent, and finally published in the Regional Gazette. However, this study highlights several problems, such as the lack of provision of appropriate facilities to overcome the various challenges faced by the younger generation, the absence of participation by religious non-governmental organizations in formulating regional policies, and the inadequate regulatory structure related to this matter. to promote youth empowerment. The results are recorded in scientific publications and shared at academic conferences.gb777